Dolgoročne strategije razvoja zdravstvene nege na področju duševnega zdravja - Sedlar, Tatjana (Obzornik zdravstvene nege, 2002)
This article discusses the psychiatric nursing vision within the sphere of mental health care. First, distinctions and interweaving among definitions of mental health, mental health crisis, mental distress, mental disorder, and mental illness are presented. In the second part three relevant documents frommental health field are summarised and discussed: 6th target Health for all for 21 st century, World health report 2001, and National program of health care of the Republic Slovenia Health for all by the year 2004. In view of the trends of deinstitutionalisation in European union the concept of community mental health is here highlighted. In the last part, the challenges of the psychiatric nursing in the new century are pointed out. The biggest of them is certainly the extension of the care from the institutions to the community.
Keywords: Bolnišnice psihiatrične; Deinstitucionalizacija; Deinstitutionalization; Duševno zdravje; Hospitals, Psychiatric; Mental Health; Mental Health Services; organizacija; organization; Organization And Administration; Psihiatrična nega; Psihiatrične službe; psihiatrija; Psychiatric Nursing; psychiatry and clinical psychology; razvoj; Trends; zdravstvena nega